Ensuring Sustainable Freight Carriage through Interoperability between Maritime and Rail Transport - Aldona Jarašūnienė (MDPI AG, 2021)
With increasing freight flows and their carriage, sustainability in the transport sector is one of today’s key challenges. With expanding geographical coverage of consumers, manufacturers and all participants in the logistics chain, sustainable carriage is becoming a considerable challenge, which can possibly be tackled by interoperability between different modes of transport. However, even in this context, there are endless difficulties, such as the compatibility of modes of transport, completion of documentation, compatibility of information systems and technologies, and the like. This article examines the importance of interoperability between maritime and rail transport in the development of international freight carriage. A theoretical assessment of maritime and rail transport interoperability covering the need for the application of information systems (IS) in the field of maritime and rail transport is presented, as well as distinguishing research problems relating to this interoperability and the presentation of key results. The quantitative and qualitative research methods applied in this article, the results of the research as well as the expert assessment of the activities of companies providing maritime and rail transport services are presented to verify the adaptation of the developed model.